Method and device for producing electrode for non-aqueous electrolyte secondary battery

By pressing in the speed-down drying area during the drying process of the lithium-ion secondary battery electrode, the problem of wrinkles and cracks in the coating film during the drying process is solved, and the effect of uniform film thickness and high battery capacity is achieved.

CN114695837BActive Publication Date: 2025-02-25PRIME PLANET ENERGY & SOLUTIONS INC
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202111610507.5
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Priority Date
2020-12-28
Filing Date
2021-12-27
Publication Date
2025-02-25
Estimated Expiration
2041-12-27

AI Technical Summary

Technical Problem

In the prior art, when manufacturing high-capacity lithium-ion secondary battery electrodes, the coating film is prone to wrinkles and cracks during the drying process, resulting in uneven film thickness and affecting battery performance.

Method used

By pressing during the drying process of the electrode composite paste, especially in the speed-down drying area, the film thickness of the coating film is controlled to be no less than 80% to suppress drying shrinkage and cracks.

Benefits of technology

The film thickness of the coating film is uniformly maintained and crack suppression is achieved, and the quality of the electrode, the high capacity and high energy density of the battery are improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN114695837B_ABST
    Figure CN114695837B_ABST
Patent Text Reader

Abstract

The present invention relates to a method and a device for manufacturing electrodes for non-aqueous electrolyte secondary batteries. The electrode manufacturing method disclosed herein includes: a step of preparing an electrode composite paste containing at least an active material and a solvent, a step of applying the electrode composite paste to the surface of a current collector, and a step of drying a coating formed by the electrode composite paste applied to the current collector. The drying step includes a waste heat zone for raising the temperature of the coating, a constant speed drying zone for keeping the temperature of the coating constant, and a speed reduction drying zone for raising the temperature of the coating again after the constant speed drying zone. The electrode manufacturing method is characterized in that the coating is pressed at least once in the speed reduction drying zone, and the pressing is performed under conditions where the film thickness is not less than 80% when the film thickness of the coating before pressing is set to 100%.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to a method for producing an electrode for a non-aqueous electrolyte secondary battery and an electrode production device for producing the electrode. Background Art

[0002] Compared with existing batteries, non-aqueous electrolyte secondary batteries such as lithium ion secondary batteries are lightweight and have high energy density, so they can be preferably used as high-output power supplies for vehicle mounting, or power supplies for personal computers and mobile terminals. In particular, lithium ion secondary batteries can be preferably used as high-output power supplies for driving vehicles such as electric vehicles (BEV), hybrid electric vehicles (HEV), and plug-in hybrid electric vehicles (PHEV).

[0003] The electrode of a non-aqueous electrolyte secondary battery generally comprises a long current collector and an electrode composite layer formed on the current collector. The electrode can be typically produced by coating an electrode composite containing an electrode active material and a solvent on the current collector and drying the coating.

[0004] Non-aqueous electrolyte secondary batteries are required to have higher performance, and as one of the guidelines for this performance improvement, higher capacity is sought. As a method of increasing the capacity of non-aqueous electrolyte secondary batteries, for example, electrodes can be made thicker than before.

[0005] When the electrode composite (coating) is applied thickly to the collector and dried in order to thicken the electrode, the drying shrinkage of the coating also increases, and thus there is a tendency for wrinkles and cracks to form on the dried coating. The drying period can generally be divided into three areas: a residual heat area where the temperature of the electrode composite (coating) on ​​the collector rises to the evaporation (volatization) temperature of the solvent, a constant speed drying area where the temperature of the electrode composite (coating) is kept constant at the evaporation (volatization) temperature of the solvent, and a reduced speed drying area where the temperature of the electrode composite (coating) rises to the temperature of the drying furnace. In particular, in the constant speed drying area, since the solvent evaporates (volatizes) rapidly, the shrinkage of the coating is large, and tensile stress is likely to remain inside the coating. Therefore, Patent Document 1 discloses a method of arranging a barrel-shaped conveying roller in the constant speed drying area to prevent residual tensile stress, thereby preventing cracks in the composite of the electrode composite (coating) after drying.

[0006] Prior art literature

[0007] Patent Literature

[0008] Patent Document 1: Japanese Patent Application Publication No. 2015-46410 Summary of the invention

[0009] However, in the method of Patent Document 1, since the electrode composite material (coating film) is dried in a state bent by a barrel-shaped conveying roller, the electrode composite material flows to both ends, resulting in an electrode with a thin center and thick ends (i.e., uneven film thickness). Electrodes with uneven film thickness may cause deviations in battery capacity and uneven reactions. Therefore, a method for manufacturing a high-quality electrode that allows a coating film thicker than before to be dried uniformly and without cracks after drying is sought.

[0010] The present invention has been made in view of the above circumstances, and its main object is to provide a method for manufacturing a high-quality electrode in which the film thickness is uniformly maintained and the generation of cracks is suppressed. In addition, another object is to provide an electrode manufacturing device used in the electrode manufacturing method.

[0011] In order to achieve the above-mentioned purpose, a method for manufacturing an electrode for a non-aqueous electrolyte secondary battery disclosed herein is provided. The manufacturing method disclosed herein includes the following steps: a step of preparing an electrode composite paste containing at least an active material and a solvent; a step of applying the electrode composite paste on a current collector; and a step of drying a coating film formed by the electrode composite paste applied on the current collector. The drying step includes a residual heat area, a constant speed drying area, and a speed reduction drying area. Here, the residual heat area is an area where the temperature of the coating film rises, the constant speed drying area is an area where the temperature of the coating film is constant, and the speed reduction drying area is an area where the temperature of the coating film rises again after the constant speed drying area. The coating film is pressed at least once in the speed reduction drying area, and the pressing is performed under the condition that the film thickness is not less than 80% when the film thickness of the coating film before pressing is set to 100%.

[0012] According to this configuration, the coating composed of the electrode composite material paste is pressed in the deceleration drying area, so the force of contraction in the thickness direction is exerted, and the force of contraction in the width and depth directions is suppressed. As a result, the force of the coating pulling the collector is also suppressed, which can prevent the bending of the collector and make the coating dry evenly. In addition, the force of contraction is alleviated, so that the generation of cracks is suppressed. That is, the film thickness of the coating is uniformly maintained and the generation of cracks is suppressed. The manufacture of high-quality electrodes can be achieved.

[0013] In a preferred embodiment of the production method disclosed herein, the pressing in the falling rate drying region is performed under conditions where the film thickness becomes thinner by 0.1% to 10% when the film thickness of the coating film before the pressing is set to 100%.

[0014] According to this configuration, even when pressing is performed in the drying step, the coating film can be pressed appropriately, and an electrode can be manufactured in which the film thickness is kept uniform and the occurrence of cracks is suppressed.

[0015] In a preferred embodiment of the production method disclosed herein, the average film thickness of the coating film when the electrode composite material paste is applied is 200 μm to 600 μm.

[0016] According to this configuration, even if the average thickness of the coating film is relatively thick, an electrode can be manufactured in which the film thickness is kept uniform and the occurrence of cracks is suppressed, so an electrode that achieves both high capacity and high quality can be manufactured.

[0017] A preferred embodiment of the production method disclosed herein is characterized in that the pressing is performed a plurality of times in the falling rate drying zone.

[0018] According to this configuration, pressing can be performed according to the drying state of the coating film, so that the occurrence of cracks can be more appropriately suppressed and the coating film can be dried in a uniform state.

[0019] In order to achieve the above other purposes, a manufacturing device of an electrode disclosed herein is provided. The electrode manufacturing device disclosed herein is an electrode manufacturing device for manufacturing an electrode used in a non-aqueous electrolyte secondary battery having an electrode body and a non-aqueous electrolyte, wherein the electrode body has a sheet-shaped positive electrode having a positive electrode composite layer formed on a long positive electrode collector and a sheet-shaped negative electrode having a negative electrode composite layer formed on a long negative electrode collector, and the electrode manufacturing device comprises: a conveying section for conveying the long collector; a coating section for coating an electrode composite paste containing at least an active material and a solvent on the long collector conveyed by the conveying section; and a drying section for drying a coating film composed of the electrode composite paste coated on the collector. The drying section comprises, from the upstream side in the conveying direction, a residual heat zone for increasing the temperature of the coating film, a constant speed drying zone for maintaining the temperature of the coating film constant, and a speed reduction drying zone for increasing the temperature of the coating film again after the constant speed drying zone. The speed reduction drying zone is provided with a pressing device for pressing the coating film at least once, and the pressing device is configured to perform pressing under the condition that the film thickness will not be less than 80% when the film thickness of the coating film before pressing is set to 100%.

[0020] According to the electrode manufacturing device, the manufacturing method disclosed herein can be appropriately implemented. That is, since the coating film is pressed by the pressing device in the speed reduction drying area, the drying shrinkage of the coating film can be suppressed. As a result, the film thickness of the dried coating film (electrode) is uniformly maintained and the generation of cracks is suppressed. The manufacturing of high-quality electrodes can be achieved.

[0021] In a preferred embodiment of the production apparatus disclosed herein, the pressing device performs pressing under conditions where the film thickness becomes thinner by 0.1% to 10% when the film thickness of the coating film before pressing is set to 100%.

[0022] According to this configuration, even when the coating film is pressed by the pressing device in the falling rate drying zone, it is possible to appropriately press without the coating film adhering to the pressing device.

[0023] In a preferred embodiment of the production apparatus disclosed herein, the average conveying speed in the falling speed drying zone is 0.5 m / min to 100 m / min.

[0024] According to this configuration, the conveying speed of the collector (typically a long sheet-shaped collector) coated with the coating can be appropriately controlled. Therefore, the drying time of the coating can be easily optimized in each area. Thus, the generation of cracks can be further suppressed.

[0025] In a preferred embodiment of the production apparatus disclosed herein, a plurality of the pressing devices are provided in the speed-falling drying zone along the conveying direction.

[0026] According to this configuration, the coating film can be pressed at a more appropriate timing, and the occurrence of cracks can be further suppressed. BRIEF DESCRIPTION OF THE DRAWINGS

[0027] Figure 1 This is a graph schematically showing the change over time of the solid content ratio in the coating film and the coating film temperature.

[0028] Figure 2 The drawings schematically show the drying process of a coating film in a conventional method, wherein (a) shows the state before drying, (b) shows the state in a constant-rate drying region, (c) shows the state in a decreasing-rate drying region, and (d) shows the state after drying.

[0029] Figure 3 The drawings schematically show the drying process of a coating film according to one embodiment, wherein (a) shows the state before drying, (b) shows the state in a constant-rate drying region, (c) shows the state in a decreasing-rate drying region, and (d) shows the state after drying.

[0030] Figure 4 It is a diagram schematically showing an electrode manufacturing apparatus according to one embodiment.

[0031] Figure 5 It is a diagram schematically showing a drying section included in an electrode manufacturing apparatus according to an embodiment.

[0032] Figure 6 This is a diagram schematically showing a drying section included in an electrode manufacturing apparatus according to still another embodiment.

[0033] Figure 7 It is a longitudinal cross-sectional view schematically showing a nonaqueous electrolyte secondary battery according to one embodiment.

[0034] Figure 8This is a diagram schematically showing the structure of a wound electrode body of a non-aqueous electrolyte secondary battery according to one embodiment.

[0035] Explanation of symbols

[0036] 1 Non-aqueous electrolyte secondary battery

[0037] 10 Current Collector

[0038] 20 Coating

[0039] 22 Solid materials

[0040] 24 Solvent

[0041] 30 Battery housing

[0042] 32 Safety valve

[0043] 42 Positive terminal

[0044] 42a Positive electrode collector plate

[0045] 44 Negative terminal

[0046] 44a Negative electrode collector plate

[0047] 50 Positive

[0048] 52 positive electrode collector

[0049] 54 Positive electrode composite layer

[0050] 56 Positive electrode current collector exposed part

[0051] 60 Negative electrode

[0052] 62 negative electrode collector

[0053] 64 Negative electrode composite layer

[0054] 66 Negative electrode current collector exposed part

[0055] 70 Isolation

[0056] 80 Wound electrode body

[0057] 100 Electrode manufacturing device

[0058] 110 Conveying Department

[0059] 112 Current collector supply device

[0060] 114 Conveyor guide

[0061] 120 Coating Department

[0062] 122 Storage Tanks

[0063] 124 Pumps

[0064] 126 Coating device

[0065] 128 Support Roller

[0066] 130 Drying Section

[0067] 132 Drying furnace

[0068] 132a Waste heat area

[0069] 132b Constant speed drying area

[0070] 132c Decrease speed drying area

[0071] 134 Heating Heater

[0072] 136 Pressing device

[0073] 136a Pressing device

[0074] 136b Pressing device

[0075] 138 Temperature measuring device

[0076] 140 Control Department DETAILED DESCRIPTION

[0077] Hereinafter, preferred embodiments of the present invention will be described with reference to the accompanying drawings. The embodiments described here are of course not intended to specifically limit the present invention. It should be noted that matters other than those specifically mentioned in this specification and matters required for the implementation of the present invention (for example, general manufacturing processes that do not characterize the electrode manufacturing method of the present invention and general structures of non-aqueous electrolyte secondary batteries) can be grasped as design matters for those skilled in the art based on the prior art in this field. The present invention can be implemented based on the contents disclosed in this specification and the technical common sense in this field. In addition, the symbol X in each figure represents the "width direction" and the symbol Z represents the "thickness direction". It should be noted that the dimensional relationship (length, width, thickness, etc.) does not reflect the actual dimensional relationship.

[0078] In addition, in this specification, the expression "A to B (wherein A and B are arbitrary values)" which shows a range means A or more and B or less.

[0079] In this specification, "secondary battery" refers to a general storage device that can be repeatedly charged, including so-called storage batteries (i.e. chemical batteries) such as lithium-ion secondary batteries, nickel-metal hydride batteries, nickel-cadmium batteries, and electric double-layer capacitors (i.e. physical batteries). In addition, in this specification, "non-aqueous electrolyte secondary battery" refers to a general storage device that can be repeatedly charged using a non-aqueous electrolyte, and is a term that includes storage elements such as so-called storage batteries and electric double-layer capacitors. In addition, in this specification, "lithium-ion secondary battery" refers to a non-aqueous electrolyte secondary battery that uses lithium ions as charge carriers and realizes charging and discharging by the movement of charges accompanying lithium ions between positive and negative electrodes.

[0080] <Electrode Manufacturing Method>

[0081] The method for manufacturing an electrode for a non-aqueous electrolyte secondary battery disclosed herein generally includes the following three steps: (1) a step of preparing an electrode composite paste; (2) a step of applying the electrode composite paste; and (3) a step of drying a coating formed by the electrode composite paste. Moreover, the step (3) of drying a coating formed by the electrode composite paste is characterized in that it includes the following three areas: (i) a residual heat area, (ii) a constant speed drying area, and (iii) a speed reduction drying area, and the coating is pressed in the speed reduction drying area (iii). Therefore, there is no particular limitation on other steps, and the same structure as the previous manufacturing method can be used. It should be noted that in this specification, "area" can also be interpreted as "stage". In addition, in addition to these steps, other steps may be included at any stage. Each step is described below.

[0082] <Electrode material paste preparation process>

[0083] In the preparation step of the electrode composite paste, at least an electrode active material and a solvent are mixed to prepare a paste. It should be noted that in this specification, "paste" is used as a term including forms called "slurry" and "ink".

[0084] As materials for the electrode composite paste, materials that have been commonly used as materials for pastes for non-aqueous electrolyte secondary batteries, especially lithium ion secondary batteries, can be used. When preparing a positive electrode composite paste, lithium composite oxides, lithium transition metal phosphate compounds (e.g., LiFePO4), etc. can be preferably used as positive electrode active materials. Examples of lithium composite oxides include lithium nickel composite oxides, lithium cobalt composite oxides, lithium manganese composite oxides, lithium nickel manganese composite oxides (e.g., LiNi 0.5 Mn 1.5 O4), lithium nickel manganese cobalt composite oxides (e.g., LiNi 1 / 3 Co 1 / 3 Mn 1 / 3 O2) etc.

[0085] The average particle size of the positive electrode active material is not particularly limited, and is generally 30 μm or less (typically 1 μm or more and 20 μm or less, for example 5 μm or more and 15 μm or less). It should be noted that in this specification, "average particle size" refers to the particle size (D) corresponding to the cumulative frequency of 50% by volume from the side of the microparticles with a small particle size in the volume-based particle size distribution based on the general laser diffraction and light scattering method. 50 , also called median particle size).

[0086] As an example of the solvent contained in the positive electrode material paste, N-methyl-2-pyrrolidone (NMP) and the like can be preferably used.

[0087] The positive electrode composite paste may contain substances other than the positive electrode active material, such as conductive materials, binders, etc. as solid components. As conductive materials, for example, carbon black such as acetylene black (AB) and other carbon materials (such as graphite) can be cited. As binders, for example, fluorine-based binders such as polyvinylidene fluoride (PVdF), polytetrafluoroethylene (PTFE), and rubber-based binders such as styrene butadiene rubber (SBR) can be preferably used. In addition, as long as the effect of the present invention is not impaired, the positive electrode composite paste may also contain materials other than the above (such as various additives, etc.).

[0088] In this specification, “solid content” refers to the materials other than the solvent (solid materials) in the above-mentioned materials, and “solid content ratio” refers to the ratio of the solid content in the electrode composite paste obtained by mixing all the materials.

[0089] When preparing the negative electrode composite paste, as the negative electrode active material, carbon materials such as graphite, hard carbon, and soft carbon can be preferably used. The graphite can be natural graphite or artificial graphite. In addition, amorphous carbon-coated graphite whose surface is coated with an amorphous carbon film can also be used.

[0090] The average particle size of the negative electrode active material is not particularly limited, but is generally 30 μm or less (typically 1 μm or more and 20 μm or less, for example 5 μm or more and 15 μm or less).

[0091] As examples of the solvent contained in the negative electrode mixed material paste, aqueous solvents can be preferably used. The aqueous solvent refers to water or a mixed solvent mainly composed of water.

[0092] The negative electrode composite paste may contain substances other than the negative electrode active material, such as thickeners, binders, etc. as solid components. As a binder, for example, styrene butadiene rubber (SBR) or the like may be preferably used. As a thickener, for example, carboxymethyl cellulose (CMC), methyl cellulose (MC) or the like may be preferably used. In addition, the negative electrode composite paste may also contain materials other than the above (such as various additives, etc.) as long as the effect of the present invention is not impaired.

[0093] The solid content of the electrode material paste is not particularly limited as long as the paste can be stably applied, but is preferably 30 to 80% by mass, more preferably 35 to 75% by mass, and even more preferably 40 to 70% by mass.

[0094] From the viewpoint of energy density, the proportion of the electrode active material in the solid content of the electrode composite paste is preferably approximately 50% by mass or more, for example, more preferably 80% by mass to 99% by mass, and further preferably 85% by mass to 95% by mass. In addition, the proportion of the binder in the solid content of the electrode composite paste is preferably, for example, 0.1% by mass to 15% by mass, and more preferably 1% by mass to 10% by mass. In addition, in the case of various additives such as thickeners, the proportion of the additive in the solid content of the paste is preferably, for example, less than 7% by mass, and more preferably less than 5% by mass.

[0095] The electrode composite material paste can be prepared by mixing the materials such as the above-mentioned electrode active material, solvent, other additives using a known mixing device in the past. As the above-mentioned mixing device, for example, a ball mill, a roller mill, a kneader, a homogenizer, etc. can be enumerated. In addition, the order of mixing the above-mentioned materials is not particularly limited, for example, all the materials can be put into the solvent at one time, or they can be divided into multiple inputs.

[0096] <Electrode material paste coating process>

[0097] The electrode material paste can be applied by applying the electrode material paste on the current collector using a conventionally known coating device, such as a gravure coater, a comma coater, a slit coater, and a die coater.

[0098] The current collector can be any metal current collector used as the current collector of this battery without any particular limitation. The positive electrode current collector to which the positive electrode composite paste is applied is made of, for example, a metal material having good electrical conductivity, such as aluminum, nickel, titanium, stainless steel, etc. Aluminum (such as aluminum foil) is particularly preferred. The thickness of the positive electrode current collector is not particularly limited, but is generally 5 μm to 30 μm, preferably 10 μm to 20 μm.

[0099] The negative electrode current collector to which the negative electrode composite paste is applied is made of, for example, a metal material having good conductivity, such as copper, an alloy mainly composed of copper, nickel, titanium, stainless steel, etc. Copper (such as copper foil) is particularly preferred. The thickness of the negative electrode current collector is not particularly limited, but is generally 5 μm to 20 μm, preferably 8 μm to 15 μm.

[0100] From the viewpoint of high capacity of the battery, the average film thickness of the coating when applied to the collector is set thicker than before, and is required to be 200 μm or more. For example, it is preferably 250 μm or more, and more preferably 300 μm or more. When the average film thickness of the coating is too thick, the drying time becomes too long, and therefore, the upper limit of the average film thickness of the coating is preferably 600 μm or less, and more preferably 550 μm or less. When the average film thickness of the coating is thicker than before, cracks are easily generated in the deceleration drying area. Therefore, the effect of the present invention can be further exerted.

[0101] <Coating drying process>

[0102] The drying step is a step of drying the coating film to remove the solvent and form an electrode composite material layer. Figure 1 This is a diagram schematically showing the change over time of the coating film temperature and the coating film solid content ratio in a general drying process. Figure 2 and Figure 3 This is a diagram schematically showing a process in which the coating film 20 immediately after being applied to the current collector 10 is dried to evaporate (volatize) the solvent 24 . Figure 2 and Figure 3 (a) shows the state before drying, (b) shows the state in the constant speed drying area, (c) shows the state in the decreasing speed drying area, and (d) shows the state after drying. Figures 1 to 3 The drying step of the paste according to one embodiment will be described.

[0103] When the coating film 20 composed of the electrode composite material paste containing a solvent is placed in a drying furnace in a stable state and dried, as shown in FIG. Figure 1 As shown in FIG. 1 , the drying process is roughly divided into three regions (stages) according to the change in the coating temperature. Region (i) is the "residual heat region" in which the coating temperature is roughly linearly increased to the evaporation temperature (volatization temperature) of the solvent. Region (ii) is the "constant rate drying region" in which the coating temperature is kept constant at the evaporation temperature (volatization temperature) of the solvent. Region (iii) is the "reduced rate drying region" in which the coating temperature is increased again after the constant rate drying region.

[0104] (i) Waste heat area

[0105] The residual heat area is typically an area where the coating temperature of the coating 20 in a room temperature environment rises to the evaporation (volatization) temperature of the solvent 24. At this time, the solid material 22 mainly composed of electrode active materials and binders is in a state of being dispersed in the solvent. (i) In the residual heat area, since the coating temperature does not reach the evaporation temperature of the solvent 24, the solvent hardly evaporates. Therefore, the solid content rate of the coating 20 is also kept roughly constant. The solid content rate at this time varies depending on the solid material 22 and solvent 24 contained in the coating 20, so it is not particularly limited, and is typically 30% to 60% by mass (for example, 45% to 55% by mass).

[0106] (ii) Constant drying area

[0107] The constant drying rate region is a region where the coating film temperature is kept constant at the evaporation temperature (volatization temperature) of the solvent 24. (ii) In the constant drying rate region, the coating film temperature reaches the evaporation temperature of the solvent 24. Figure 2 As shown in (b), the solvent 24 evaporates from the coating surface. Figure 2 The force of contraction in the direction indicated by the arrow in (b) acts. In addition, since the solvent 24 evaporates from the coating film 20, the solid content of the coating film 20 increases. The solid content is as follows: Figure 1 As shown, the solid content increases approximately linearly in proportion to time. The solid content at this time changes rapidly and cannot be generalized, but is typically 40% to 70% by mass (eg, 55% to 65% by mass).

[0108] (iii) Speed ​​reduction drying area

[0109] The falling rate drying area is an area where the coating film temperature maintained constant in the (ii) constant rate drying area is raised again to the temperature of the drying furnace. The state of the coating film 20 in the (iii) falling rate drying area is typically a state where the solvent 24 present near the surface of the coating film 20 has been substantially evaporated, and the solvent 24 present between the solid materials 22 constituting the coating film 20 has evaporated. At this time, in the coating film 20, the solid materials 22 along the Figure 2 As a result, the current collector 10 is also pulled by the contraction force of the coating film 20, as shown in the arrows of (c). Figure 2 As shown in (d), the center of the current collector 10 is curved into a concave shape. In addition, since the contraction force remains inside the coating film 20, cracks are generated in the coating film 20 from the gaps in the coating film 20. Figure 2 In (c), the shrinkage direction of the solid material 22 is shown in two dimensions, but this is due to the Figure 2 (c) is depicted as a schematic plan view, but in reality, a force that contracts in three-dimensional directions acts on the solid material 22 .

[0110] The solid content of the coating film 20 is as follows: Figure 1 As shown, it increases gently compared with the constant drying region (ii). The solid content ratio at this time varies depending on the solid material 22 and the solvent 24 contained in the coating film 20, and is therefore not particularly limited, but is typically 60% to 95% by mass (e.g., 75% to 90% by mass). If the coating film 20 has a solid content ratio within the above range, it can be pressed appropriately without the coating film 20 adhering to the pressing device.

[0111] In the manufacturing method disclosed herein, (iii) in the falling rate drying zone, such as Figure 3 (iii) When pressing in the drying zone at a decreasing speed, the contraction force acts only in the downward direction as shown by the arrow, and the contraction force of the solid material 22 is relaxed in the X direction. Figure 3 As shown in (d), the coating 20 can be dried in a uniform state without bending the central portion of the collector 10 into a concave shape. Therefore, an electrode with uniform film thickness can be obtained. In addition, the contraction force inside the coating 20 is alleviated, and the generation of cracks can be suppressed. That is, by pressing in the deceleration drying area, the production of high-quality electrodes in which the generation of cracks is suppressed and the film thickness is uniformly maintained can be achieved.

[0112] The drying method in the drying step is not particularly limited as long as it is a method having the above-mentioned three zones, and examples thereof include conventionally known methods such as hot air drying and infrared drying.

[0113] The drying temperature (temperature in the drying furnace) in the drying process varies depending on the type of solvent 24 used, and therefore, is not particularly limited, and is set to, for example, 50° C. or higher, typically, 70° C. or higher, and more preferably, 100° C. or higher. In particular, when a solvent with a relatively high boiling point (e.g., an aqueous solvent) is used, it can be set to 120° C. or higher, for example, 140° C. or higher. The upper limit of the drying temperature is not particularly limited, and from the viewpoint of reducing production costs, it is set to, for example, 200° C. or lower, typically, 190° C. or lower, and more preferably, 180° C. or lower.

[0114] The pressing conditions in the speed-down drying region require that the film thickness of the coating film 20 after pressing is not less than 80% when the film thickness of the coating film 20 before pressing is set to 100%. Typically, it is preferably performed under the condition of thinning by 0.1% to 15%, for example, it is more preferably performed under the condition of thinning by 0.1% to 10%, and further preferably performed under the condition of thinning by 0.5% to 8%. If the pressing conditions are within the above range, an electrode with uniform film thickness can be manufactured without applying excessive pressing pressure to the coating film 20, and an electrode with suppressed crack generation can be obtained.

[0115] The conveying speed in the deceleration drying zone is not particularly limited, and is typically preferably set to 0.1 m / min or more from the viewpoint of improving productivity. For example, it is preferably set to 0.3 m / min or more, and more preferably set to 0.5 m / min or more. When the drying speed is too fast, cracks are easily generated in the coating film 20, and therefore, typically, it is preferably set to 100 m / min or less. For example, it is preferably set to 90 m / min or less, and more preferably set to 80 m / min or less.

[0116] After the drying process, a pressing process may be performed for the purpose of adjusting the unit area weight and density of the electrode composite layer. The pressing process may be performed using a roller press or the like according to a conventionally known method. It should be noted that the pressing process referred to herein refers to a pressing process performed under the condition that the thickness of the electrode composite layer before the pressing process is set to 100% and is approximately 70% or less in thickness (e.g., the linear pressure during rolling is 10 kN / cm or more).

[0117] <Electrode manufacturing equipment>

[0118] According to the technology disclosed herein, an electrode manufacturing device for manufacturing an electrode is provided. Figure 4 1 is a diagram schematically showing an electrode manufacturing apparatus 100 according to an embodiment. The electrode manufacturing apparatus 100 can be used to manufacture an electrode for a positive electrode (positive electrode) and an electrode for a negative electrode (negative electrode) of a non-aqueous electrolyte secondary battery (typically a lithium ion secondary battery). Figure 4 As shown, the conveying unit 110, the coating unit 120, the drying unit 130 and the control unit 140 are provided. These are sequentially arranged along a preset conveying path. The control unit 140 is electrically connected to the conveying unit 110, the coating unit 120 and the drying unit 130 to control them. Figure 1 The electrode manufacturing apparatus 100 shown typically forms an electrode material layer by coating an electrode material paste on the current collector 10 while conveying the long current collector 10 in the longitudinal direction and removing the solvent by drying. Figures 4 to 6 The arrow in represents the conveying direction.

[0119] The control unit 140 is composed of, for example, a microcomputer. The hardware configuration of the microcomputer is not particularly limited. The hardware configuration of the microcomputer includes, for example, an interface capable of transmitting and receiving data with an external device, a central processing unit (CPU) that executes commands of a control program, a ROM (read only memory) that stores programs executed by the CPU, a RAM (random access memory) used as a work area for developing programs, and a storage unit such as a memory that stores the above-mentioned programs and various data, but is not limited thereto.

[0120] The conveying unit 110 conveys the collector 10 along the conveying path. The conveying unit 110 includes, for example, a collector supply device 112 for supplying the collector 10 and a plurality of conveying guides 114. The collector supply device 112 is configured to roll up the long collector 10 on a winding core in advance, and a specified amount of the collector 10 is supplied from the collector supply device 112 under the control of the control unit 140. As the collector 10, a material with good conductivity and stable existence inside the battery can be used, and light weight, required mechanical strength, ease of processing, etc. are required. As the above-mentioned material, a metal foil composed of the above-mentioned metal with good conductivity (such as copper, aluminum) can be preferably used.

[0121] The conveying unit 110 may include a tension control mechanism for adjusting the current collector 10 in such a manner that a predetermined tension is applied thereto. As the tension control mechanism, for example, an automatic tension control device of a tension adjustment roller type may be cited. In addition, the conveying unit 110 may include a position adjustment mechanism for adjusting the position of the current collector 10 in the width direction. As the position adjustment mechanism, for example, a so-called EPC (edge ​​position control) which is a combination of an edge inspection device (edge ​​sensor) and a position correction device (position controller) may be cited. The above-mentioned tension control mechanism and position adjustment mechanism are, for example, electrically connected to the control unit 140 and controlled.

[0122] It should be noted that the configuration of the device, control, etc. of the transport unit 110 may be the same as that of the conventional device and control, and since it does not represent the present invention, a detailed description thereof will be omitted.

[0123] The coating unit 120 coats the electrode composite paste on the collector 10. The coating unit 120 includes, for example, a storage tank 122, a pump 124, a coating device 126, and a support roller 128. The storage tank 122 is a tank for storing the electrode composite paste produced as described above. The inner wall of the storage tank 122 is preferably a material with excellent corrosion resistance for the stored electrode composite paste. As such a material, stainless steel can be cited, for example. The pump 124 is a device for transferring the electrode composite paste from the storage tank 122 to the coating device 126. The pump 124 is connected to the storage tank 122 via a pipe. The electrode composite paste stored in the storage tank 122 is sucked up from the discharge port of the storage tank 122 at a certain flow rate by the pump 124, and is transferred to the coating device 126. The coating device 126 is a device for coating the electrode composite paste on the collector 10. As the coating device 126 , for example, a conventionally known device such as a slit coater, a gravure coater, a die coater, or a comma coater can be used. The support roller 128 is disposed along the conveyance path and is a roller that supports the current collector 10 .

[0124] exist Figure 4 In the example shown, a die coater is used as the coating device 126. The current collector 10 is conveyed along the conveying path and supported by the support roller 128. The coating device 126 is controlled by the control unit 140, for example, so that the electrode composite paste can be continuously applied to the current collector 10 at a predetermined weight per unit area and thickness.

[0125] In addition to the above-mentioned devices, the coating unit 120 may also be equipped with other devices used in such coating devices. For example, a filtering device for removing foreign matter (such as metal foreign matter) in the electrode composite paste may be provided between the pump 124 and the coating device 126 .

[0126] The drying unit 130 dries the coating film 20 composed of the electrode material paste to form an electrode material layer on the current collector 10. The drying unit 130 is, for example, Figure 5 As shown, the drying furnace 132, a heating heater 134, a pressing device 136 and a temperature measuring device 138 are provided. The drying furnace 132 has a residual heat area 132a for raising the coating temperature to the evaporation temperature (volatilization temperature) of the solvent, a constant speed drying area 132b for maintaining the coating temperature constant, and a speed reduction drying area 132c for raising the coating temperature again after the constant speed drying area, from the upstream side in the conveying direction.

[0127] As long as the drying furnace 132 has the above-mentioned three zones (stages), the heating method is not particularly limited, and for example, a hot air drying furnace, an infrared drying furnace, or other conventionally known devices may be used. The heating heater 134 is a heat source, and for example, when the drying furnace 132 is a hot air drying furnace, it is a device that sprays heated gas. At this time, the gas sprayed from the heating heater 134 is not particularly limited, and may be an inert gas such as nitrogen or helium. The pressing device 136 is a device that presses the coating film 20 in the speed reduction drying area 132c. The temperature measuring device 138 is a device that measures the temperature of the coating film inside the drying furnace 132. Figure 5 As shown by the middle dotted line, the heating heater 134 , the pressing device 136 , and the temperature measuring device 138 are electrically connected to the control unit 140 .

[0128] The drying temperature (temperature in the drying furnace) of the drying furnace 132 may be the same or different between the residual heat area 132a, the constant speed drying area 132b and the speed reduction drying area 132c. For example, the coating temperature may be continuously measured by the temperature measuring device 138, and the control unit 140 controls the heating heater 134 based on the value. From the viewpoint of improving productivity, the drying temperature (temperature in the drying furnace) is preferably set to 50°C or more, for example, more preferably 80°C or more, and further preferably 100°C or more. In particular, when using a solvent with a higher boiling point (such as an aqueous solvent), it can be set to 120°C or more, for example, 140°C or more. From the viewpoint of preventing cracking of the coating and oxidation of the collector 10 (metal foil), the upper limit of the drying temperature (temperature in the drying furnace) is preferably set to 200°C or less, more preferably 190°C or less, and further preferably 180°C or less.

[0129] Depending on the types of solid materials 22 and solvents 24 contained in the coating film 20 and the conditions of the drying furnace 132, the coating film temperature of the coating film 20 may be too low or too high than the desired temperature at the position of each region. Therefore, the coating film temperature is continuously measured by the temperature measuring device 138 as described above, and the heating heater 134 is controlled by the control unit 140 based on the value. That is, at a predetermined position (for example, the temperature measuring device 138 on the upstream side), when the coating film temperature is too low, the temperature of the heating heater 134 arranged in the constant speed drying area 132b is increased, and when the coating film temperature is too high, the temperature of the heating heater 134 arranged in the constant speed drying area 132b is reduced, thereby stabilizing the state of the coating film in the speed reduction drying area 132c.

[0130] The conveying speed of the conveying section 110 in the drying furnace 132 may be the same or different between the residual heat area 132a, the constant speed drying area 132b and the speed reduction drying area 132c. In a preferred embodiment, the conveying speed is preferably kept approximately constant in three intervals (for example, the conveying speed is set to ±0.1 m / min). From the viewpoint of preventing the coating film from cracking, the conveying speed is preferably set to less than 100 m / min, more preferably less than 90 m / min, and further preferably less than 80 m / min. From the viewpoint of production cost, it is preferably set to more than 0.1 m / min, and further preferably more than 0.5 m / min.

[0131] The form of the pressing device 136 is not particularly limited as long as it is a device that can press the coating film 20 under the conditions in the above range. For example, the pressing may be performed using a roller press or a flat plate press. Figure 5 In the example shown, the coating film 20 is pressed by passing the current collector 10 and the coating film 20 between rollers arranged vertically. When the pressing device 136 is a roller mill, the diameter of the roller is preferably 20 mm to 60 mm, more preferably 30 mm to 50 mm.

[0132] The pressing by the pressing device 136 is adjusted to press under the condition that the film thickness of the coating 20 after pressing is not less than 80% when the film thickness of the coating 20 before pressing is set to 100%. As a specific linear pressure of the rolling mill, it varies according to the material of the positive electrode active material contained in the coating 20 and the drying state of the coating 20, and therefore, it is not particularly limited, for example, 0.1 kN / cm (about 10 kg / cm) or less. It should be noted that the pressing is carried out inside the drying furnace 132, which is different from the pressing of the general pressing process performed after the drying process. The linear pressure of the rolling mill used in the pressing process is typically 10 kN / cm (about 1000 kg / cm) or more.

[0133] The pressing device 136 is as follows Figure 6 As shown, a plurality of (pressing devices 136a, 136b) may be provided in the speed-down drying area 132c along the conveying direction. When a plurality of press devices 136 are provided, the pressing pressures of the press devices 136a, 136b may be of the same magnitude or of different magnitudes. The pressing pressure of the press device 136a disposed on the upstream side of the conveying direction may be set to be greater than the pressing pressure of the press device 136b disposed on the downstream side of the conveying direction. According to this configuration, shrinkage of the coating film can be more appropriately prevented.

[0134] It should be noted that Figure 5 In the example shown, the configuration includes two pressing devices 136 , but two or more pressing devices 136 may be provided.

[0135] When a plurality of pressing devices 136 are provided, only a more appropriate pressing device 136 can be used for pressing. Figure 6 The pressing device 136a shown in the figure performs pressing, or only the pressing device 136b may perform pressing. The pressing can be performed by the control unit 140 based on the coating film temperature measured by the temperature measuring device 138.

[0136] By drying the current collector 10 coated with the electrode mixture paste in the drying unit 130, the solvent is evaporated (volatilized) and removed from the paste (coating film) on the current collector 10. Thus, an electrode including an electrode mixture layer on the current collector 10 can be manufactured.

[0137] The manufacturing method and electrode manufacturing device disclosed herein can effectively produce high-quality electrode composite materials. In addition, the manufactured electrode is an electrode composed of a thicker coating than in the past, and therefore has the advantage of high capacity. Therefore, when a secondary battery is constructed using the electrode, a high-capacity secondary battery can be obtained.

[0138] The electrode produced as above can be used in the manufacture of a non-aqueous electrolyte secondary battery. Figure 7 and Figure 8 A configuration example of a nonaqueous electrolyte secondary battery produced using an electrode obtained by the production method disclosed herein will be described.

[0139] In the following embodiments, a lithium-ion secondary battery having a wound electrode body is described in detail as an example, but the present invention is not intended to be limited to this embodiment. For example, a stacked structure electrode body having a stacked structure in which a plurality of positive and negative electrode sheets are stacked on each other via a separator may also be preferably applied.

[0140] Figure 7 The non-aqueous electrolyte secondary battery 1 shown is constructed by accommodating a flat-shaped wound electrode body 80 and a non-aqueous electrolyte (not shown) in a sealed box-shaped battery case 30. The battery case 30 is provided with a positive terminal 42 and a negative terminal 44 for external connection, and a thin-walled safety valve 32 set in a manner to release the internal pressure when the internal pressure of the battery case 30 rises to a specified level or above. In addition, the battery case 30 is provided with a liquid injection port (not shown) for injecting a non-aqueous electrolyte. The positive terminal 42 is electrically connected to the positive electrode collector plate 42a. The negative terminal 44 is electrically connected to the negative electrode collector plate 44a. The material of the battery case 30 is preferably a metal material with high strength, light weight and good thermal conductivity. As such a metal material, for example, aluminum, steel, etc. can be cited.

[0141] The wound electrode body 80 is as follows Figure 7 and Figure 8As shown, it has a form in which a long sheet-shaped positive electrode 50 and a long sheet-shaped negative electrode 60 are overlapped and wound in the long side direction via a long sheet-shaped separator 70. The positive electrode 50 has a structure in which a positive electrode composite layer 54 is formed on one side or both sides of a long sheet-shaped positive electrode collector 52 along the long side direction. The negative electrode 60 has a structure in which a negative electrode composite layer 64 is formed on one side or both sides of a long sheet-shaped negative electrode collector 62 along the long side direction. A portion (i.e., a positive electrode collector exposed portion 56) is provided along one edge portion in the width direction of the positive electrode collector 52, along which the positive electrode composite layer 54 is not formed and the positive electrode collector 52 is exposed. A portion (i.e., a negative electrode collector exposed portion 66) is provided along another edge portion in the width direction of the negative electrode collector 62, along which the negative electrode composite layer 64 is not formed and the negative electrode collector 62 is exposed. The positive electrode current collector plate 42 a and the negative electrode current collector plate 44 a are joined to the positive electrode current collector exposed portion 56 and the negative electrode current collector exposed portion 66 , respectively.

[0142] The positive electrode 50 and the negative electrode 60 can use the positive electrode 50 and the negative electrode 60 obtained by the above-mentioned manufacturing method. It should be noted that in this configuration example, the positive electrode 50 and the negative electrode 60 have electrode composite layers (positive electrode composite layer 54 and negative electrode composite layer 64) formed on both sides of the collector 10 (positive electrode collector 52 and negative electrode collector 62).

[0143] As the separator 70, for example, a porous sheet (film) made of a resin such as polyethylene (PE), polypropylene (PP), polyester, cellulose, polyamide, etc. can be cited. The porous sheet can be a single-layer structure or a laminated structure of two or more layers (for example, a three-layer structure in which PP layers are laminated on both sides of a PE layer). The separator 70 can be provided with a heat-resistant layer (HRL).

[0144] The non-aqueous electrolyte can use the same non-aqueous electrolyte as the previous lithium ion secondary battery. Typically, a non-aqueous electrolyte containing a supporting salt in an organic solvent (non-aqueous solvent) can be used. As a non-aqueous solvent, organic solvents such as carbonates, esters, ethers, nitriles, sulfones, and lactones can be used without limitation. Specifically, for example, non-aqueous solvents such as ethylene carbonate (EC), diethyl carbonate (DEC), dimethyl carbonate (DMC), ethyl methyl carbonate (EMC), monofluoroethylene carbonate (MFEC), difluoroethylene carbonate (DFEC), monofluoromethyl difluoromethyl carbonate (F-DMC), and trifluorodimethyl carbonate (TFDMC) can be preferably used. Such non-aqueous solvents can be used alone or in combination of two or more. As a supporting salt, for example, lithium salts such as LiPF6, LiBF4, and LiClO4 can be appropriately used. The concentration of the supporting salt is not particularly limited, preferably 0.7 mol / L or more and 1.3 mol / L or less.

[0145] The nonaqueous electrolyte may contain components other than the nonaqueous solvent and supporting salt, such as various additives such as a gas generating agent, a film forming agent, a dispersant, and a thickener, as long as the effects of the present invention are not significantly impaired.

[0146] The non-aqueous electrolyte secondary battery 1 constructed as above can be used for various purposes. As suitable uses, a driving power source carried by vehicles such as electric vehicles (BEV), hybrid electric vehicles (HEV), and plug-in hybrid electric vehicles (PHEV) can be cited. The non-aqueous electrolyte secondary battery 1 can also be used in the form of a battery pack formed by connecting a plurality of batteries in series and / or in parallel.

[0147] Hereinafter, although the Example related to this invention is demonstrated, it is not intended that this invention is limited to the content shown in this Example.

[0148] First, a paste is obtained by mixing N-methyl-2-pyrrolidone (NMP) as a solvent, acetylene black (AB) as a conductive material, and polyvinylidene fluoride (PVdF) as a binder using a disperser. LiFePO4 (LFP) as a positive electrode active material is mixed into the paste to prepare a positive electrode composite paste. It should be noted that the positive electrode composite paste is adjusted to LFP:AB:PVdF=91.4:4.6:4 (mass ratio).

[0149] The positive electrode material paste was applied to an aluminum foil serving as a positive electrode current collector in a thickness of 500 μm.

[0150] Next, the positive electrode current collector coated with the paste was placed in a 120°C hot air drying oven (conveying speed 1 m / min) to dry and remove the solvent. Thus, a positive electrode having a positive electrode composite layer on one surface of the positive electrode current collector was prepared (Comparative Example 1).

[0151] Similarly, prepare a positive electrode collector coated with the above-mentioned paste. Put the positive electrode collector coated with the above-mentioned paste into a hot air drying furnace at 120°C (transport speed 1m / min), and press it using a pressing device in the speed reduction drying area in the hot air drying furnace. At this time, the pressing device uses a rolling mill with rollers (φ40) arranged above and below, with a linear pressure of 0.002kN / cm (about 0.2kg / cm) and 1 pressing. In addition, the solid content of the positive electrode composite paste (coating) when pressing is performed under this condition is 80% by mass. Thus, a positive electrode having a positive electrode composite layer on the surface of one side of the positive electrode collector is prepared (Example 1).

[0152] <Evaluation of electrode quality>

[0153] The state of the coating film (whether the collector is bent) was visually evaluated for Example 1 and Comparative Example 1. The area ratio of cracks in the coating film after drying, the film thickness of the coating film after drying, and the filling rate of the electrode after drying were determined. The results are shown in Table 1.

[0154] It should be noted that the area ratio of cracks in the dried coating film was calculated by observing the surface of the dried coating film using a laser microscope. The area ratio of cracks in the dried coating film was obtained by dividing the area of ​​the cracks by the area of ​​the entire coating film. The results are shown in Table 1.

[0155] The filling rate of the electrode after drying is the value obtained by dividing the true electrode density by the apparent electrode density and multiplying by 100. The true electrode density is the value calculated based on the density and content ratio of the constituent components. The apparent electrode density is the value obtained by dividing the mass (g) of the electrode (coating film after drying) by the apparent volume (cm 3 The area (cm2) of Example 1 and Comparative Example 1 in plan view was measured. 2 ) and thickness (cm), and multiply these values ​​to calculate the apparent volume.

[0156] [Table 1]

[0157] Table 1

[0158]

[0159] The coating film is dried without bending the collector, and the film thickness is uniform. In addition, as shown in Table 1, it can be seen that the pressing using the pressing device is carried out under the condition that the film thickness of Example 1 is not less than 80% when the film thickness of Comparative Example 1 is set to 100%. Moreover, it can be seen that in Example 1 where the pressing is carried out in the speed reduction drying area, no cracks are generated in the dried coating film (electrode). That is, according to the electrode manufacturing method and electrode manufacturing device disclosed herein, it is possible to achieve the manufacture of high-quality electrodes in which cracks are suppressed in the coating film (electrode) and the film thickness is uniformly maintained.

[0160] As shown in Table 1, the electrode filling rate of Example 1 is higher than that of Comparative Example 1. That is, it can be said that the energy density of the electrode of Example 1 is higher than that of Comparative Example 1.

[0161] Although specific examples of the present invention have been described in detail above, these are merely examples and do not limit the scope of the claims. The technology described in the scope of the claims includes various modifications and changes to the specific examples described above.

Claims

1. A method for manufacturing an electrode, characterized in that: A method for manufacturing an electrode for a non-aqueous electrolyte secondary battery comprises the following steps: A step of preparing an electrode material paste containing at least an active material and a solvent, The step of coating the electrode composite paste on the current collector, and A step of drying a coating film composed of the electrode composite material paste applied on the current collector; The drying process includes a residual heat area, a constant speed drying area and a decreasing speed drying area. Here, the residual heat region is a region where the temperature of the coating film rises. The constant drying area is an area where the temperature of the coating film is kept constant. The falling rate drying area is an area where the temperature of the coating film rises again after the constant rate drying area. The coating film is pressed at least once in the falling speed drying area. The average film thickness of the coating film when the electrode composite material paste is applied is 300 μm to 600 μm. The first pressing is performed under the condition that the film thickness is not less than 80% when the film thickness of the coating film before the pressing is set to 100% and the linear pressure is 0.1 kN / cm or less; Furthermore, the method further comprises the following steps: After the drying step, second pressing is performed under conditions such that the film thickness becomes 70% or less when the film thickness of the coating film before the pressing is 100%.

2. The method for manufacturing an electrode according to claim 1, wherein: The pressing in the speed-reducing drying zone is performed under the condition that the film thickness is reduced by 0.1% to 10% when the film thickness of the coating film before the pressing is set to 100%.

3. The method for manufacturing an electrode according to claim 1 or 2, characterized in that: The pressing is performed multiple times in the falling rate drying zone.

4. An electrode manufacturing device, which is an electrode manufacturing device for manufacturing an electrode used in a non-aqueous electrolyte secondary battery having an electrode body and a non-aqueous electrolyte, wherein the electrode body has a sheet-shaped positive electrode having a positive electrode composite layer formed on a long positive electrode current collector and a sheet-shaped negative electrode having a negative electrode composite layer formed on a long negative electrode current collector, the electrode manufacturing device comprising: a conveying unit for conveying the long current collector; a coating unit for coating an electrode composite paste containing at least an active material and a solvent on the elongated current collector conveyed by the conveying unit, and A drying section for drying a coating film composed of the electrode composite material paste applied on the current collector; The drying section includes, from the upstream side in the conveying direction, a residual heat zone for raising the temperature of the coating film, a constant speed drying zone for maintaining the temperature of the coating film constant, and a speed reduction drying zone for raising the temperature of the coating film again after the constant speed drying zone. The speed-down drying area is provided with a pressing device for pressing the coating film conveyed by the conveying unit. The pressing device is configured to: perform a first pressing of the coating film in the speed-down drying area at least once, The average film thickness of the coating film when the electrode composite material paste is applied is 300 μm to 600 μm. The first pressing is performed under the condition that the film thickness is not less than 80% when the film thickness of the coating film before the pressing is set to 100% and the linear pressure is 0.1 kN / cm or less; Further, the second pressing is performed under the condition that the film thickness becomes 70% or less when the film thickness of the coating film before the pressing is set to 100%.

5. The electrode manufacturing device according to claim 4, wherein: The pressing device performs pressing under conditions in which the film thickness becomes thinner by 0.1% to 10% when the film thickness of the coating film before pressing is set to 100%.

6. The electrode manufacturing device according to claim 4 or 5, wherein: The average conveying speed in the speed-down drying zone is 0.5 m / min to 100 m / min.

7. The electrode manufacturing device according to claim 4 or 5, wherein: The speed-down drying area is provided with a plurality of the pressing devices along the conveying direction.

8. The electrode manufacturing device according to claim 6, wherein: The speed-down drying area is provided with a plurality of the pressing devices along the conveying direction.

Citation Information

Patent Citations

  • Device of manufacturing battery electrode

    JP2015046410A

  • Electrode for nonaqueous battery and method for manufacturing the same

    JP2014203572A

  • Electrode for electric device, manufacturing method thereof, and electric device employing the electrode

    JP2018195587A

  • Bipolar electrode

    WO2018066390A1

  • Method for producing nonaqueous alkali metal electricity storage element

    WO2020203421A1